O ensino da produção textual escrita na formação inicial do professor de Língua Portuguesa: das bases teórico-metodológicas às ações em sala de aula - Rosa, Douglas Corrêa da (2019)
This research is centered on the initial training of the Portuguese Language teachers. Reflecting on the formation of the future teacher is, it is possible to consider the possibilities and guide that can contribute to the process of teaching and learning of language and, more directly, teaching writing, a branch of Portuguese teaching. Thus, the general objective of this dissertation was to understand how undergraduate students in Language Arts course of the Unioeste/Cascavel are prepared, from the theoretical, methodological and practical point of view, to teach writing in school. It is defended the thesis that the theoretical-methodological training of the native-language educator in initial formation guides and constitutes effective teaching practices working with the production of written texts, providing the teachers in training with the development of skills that will help them to teach the students to how to produce written texts. Therefore, the driving questions of the study were: i) In what way does the undergraduate course of Language Arts at Unioeste/Cascavel provide students with a theoretical and methodological training on the teaching of writing from a conception of language? ii) To what degree do the disciplines that contemplate educational practicums and internships provide students of undergraduate teacher training theoretical and methodological approaches to teach writing? iii) How do some students of the undergraduate course in Language Arts articulate the theoretical knowledge to the practical knowledge in what concerns the teaching of writing? The research was inserted in the field of Applied Linguistics, by means of qualitative-interpretative research, of ethnographic character, with documentary analysis. The corpus consisted of documents (Political Pedagogical Project of the Undergraduate Courses in Language Arts, education plans of some disciplines related to the teaching of Portuguese and the educational practicums and internships, lesson plans elaborated by students in their on-site activities and also their recorded data) and participant observation (both of university professors and undergraduate students’ experience on-site). The discussions were based on the theoretical perspective of the Bakhtin Circle, based on concepts such as interactionist concept of language, dialogism, utterance/word, and speech genres. In addition, it is discussed how can writing practice be didactically guided, from this theoretical conception. The results indicated that the undergraduate course at Unioeste/Cascavel has no specific discipline that deals with the teaching of writing. However, both in the PPP course and in the teaching plans of some subjects, there are indications of theoretical readings and official teaching documents that help the teacher in training to understand the disciplinary, curricular and professional knowledge related to the teaching of writing. Nevertheless, these readings are diluted over the years in the disciplines. More systematic work on teaching how to produce written texts occurs in 8 the subject of “Teaching Practice and Supervised Internship”. In the disciplines related to education practicum, although some reading and theories studies were related to the undergraduate course in teaching Portuguese, the greater part of the workload is occupied with the bureaucratic outcomes of the internship, such as the Term of Commitment, assignments, records, reports etc.). In the observation of the trainee teachers in their on-site experience, it was verified that they proposed to work with the teaching of writing, and concentrated their actions around speech genres; however, the emphasis of the work rested on the teaching of spelling and grammatical concepts. These results are certainly relevant and important to think critically about the training of our teachers. It is expected that the results obtained with this dissertation can be extended to other teaching contexts and, therefore, be encouraged to (re)think and (re) orient linguistic practices as a guiding line that would permeate all the training of professionals to acting in Portuguese teaching.